Extração de esterase de fígado suíno (PLE) - Trevisan, Henrique Celso [UNESP]; Medeiros, João Batista de [UNESP]; Lisboa, Helen Cristina Fávero [UNESP] (Sociedade Brasileira de Química, 2006)
A simple, fast and low-cost methodology was optimized, seeking preparation of a crude pig liver esterase (PLE) concentrate. Basically, the method consisted of the following steps: liver homogenization, acetone washing, enzyme extraction and purification/concentration. Starting from 1 kg of fresh liver more than 200 kU of PLE suspension were obtained after 8 hours, at an estimated cost of US$0.21/kU. The PLE concentrate thus obtained was stable, showing 96-100% of the initial activity after 7 months in refrigerator at 4°C.
Pig liver esterase (PLE) extraction
Keywords: porcine liver esterase; PLE; biocatalysis